Bioenergy research advances and applications - Gupta, Vijai Kumar; Tuohy, Maria G.; Kubicek, C. P.; Saddler, Jack; Xu, Feng (Elsevier, 2014)
Bioenergy Research: Advances and Applications brings biology and engineering together to address the challenges of future energy needs. The book consolidates the most recent research on current technologies, concepts, and commercial developments in various types of widely used biofuels and integrated biorefineries, across the disciplines of biochemistry, biotechnology, phytology, and microbiology. All the chapters in the book are derived from international scientific experts in their respective research areas. They provide you with clear and concise information on both standard and more recent bioenergy production methods, including hydrolysis and microbial fermentation. Chapters are also designed to facilitate early stage researchers, and enables you to easily grasp the concepts, methodologies and application of bioenergy technologies. Each chapter in the book describes the merits and drawbacks of each technology as well as its usefulness. The book provides information on recent approaches to graduates, post-graduates, researchers and practitioners studying and working in field of the bioenergy. It is an invaluable information resource on biomass-based biofuels for fundamental and applied research, catering to researchers in the areas of bio-hydrogen, bioethanol, bio-methane and biorefineries, and the use of microbiali processes in the conversion of biomass into biofuels. Reviews all existing and promising technologies for production of advanced biofuels in addition to bioenergy policies and research fundingCutting-edge research concepts for biofuels production using biological and biochemical routes, including microbial fuel cellsIncludes production methods and conversion processes for all types of biofuels, including bioethanol and biohydrogen, and outlines the pros and cons of each